The outcomes of microvascular decompression for primary trigeminal neuralgia: insights from a single-center experience and technical advancements - Nurimanov, Chingiz; Mammadinova, Iroda; Menlibayeva, Karashash; Kaliyev, Assylbek; Makhambetov, Yerbol; Akshulakov, Serik (Frontiers in Surgery, 2024)
Background Microvascular decompression (MVD) remains the primary surgical treatment for trigeminal neuralgia due to its positive postoperative results. This study aims to evaluate the outcomes of patients with primary trigeminal neuralgia who underwent MVD. Additionally, the paper offers a detailed explanation of the surgical methodology of MVD employed at the neurosurgical hospital in Kazakhstan. Methods The study involved 165 medical records of patients with trigeminal neuralgia who underwent MVD between 2018 and 2020. Out of these 165 patients, 90 (54.55%) were included in the final analysis and were further evaluated using the Barrow Neurological Institute pain intensity score. Various variables were analyzed, including age, sex, affected side, dermatomes, offending vessel, and surgical intervention type. Moreover, the surgical technique employed at the hospital was described. Results The average follow-up period after the MVD procedure was 32.78 ± 9.91 months. The results indicated that out of the 90 patients, 80 (88.89%) achieved a good outcome as evidenced by BNI scores I and II. It was observed that patients with affected maxillary dermatomas and those with affected ophthalmic + maxillary dermatomas were more likely to experience fair + poor postsurgery BNI scores. On the other hand, patients with neurovascular conflicts involving the maxillary + mandibular dermatomas demonstrated good BNI scores (p = 0.01). Conclusions The outcomes of MVD in patients with primary trigeminal neuralgia showed good BNI scores within this study population. The outcome depended on the affected dermatome of the trigeminal nerve with the vessel. Additionally, patient positioning, intraoperative management including small skin incisions, minimal craniotomy, and precise closure of the dura, as well as intraoperative neurolysis, may contribute to achieving good clinical and satisfactory post-surgery aesthetic outcomes.